Effects of alumina nano-particulates addition on mechanical and electrical properties of barium titanate ceramics - S. Jiansirisomboon (2018)
Ferroelectric BaTiO3/xAl2O3nanocomposite ceramics (when x = 0, 0.5, 1, 3 and 5 vol%) were fabricated from an in-house prepared BaTiO3powder and nano-sized Al2O3powder by a solid state mixed-oxide method. Densities and grain sizes of the ceramics were found to gradually decrease with increasing content of Al2O3addition. Mechanical properties such as Knoop hardness and Young's modulus of BaTiO3were found to be improved with only 0.5 vol% of Al2O3addition. Dielectric and piezoelectric properties of the nanocomposites with <1 vol% Al2O3addition could be maintained and were comparable to the values of the monolithic BaTiO3. Within the range of the BaTiO3/Al2O3nanocomposites investigated, this study suggested materials with acceptable electrical properties and better structural stability. © 2007 Elsevier B.V. All rights reserved.